Audiometric Outcomes Comparing Endoscopic Versus Microscopic Ossiculoplasty. Issue 7 (7th August 2022) - Sakai, Mark; Killeen, Daniel E.; Ma, Connie; Newcomer, Mark; Hunter, Jacob B.; Isaacson, Brandon; Kutz, Joe Walter
Abstract : Objective: To assess endoscopic and microscopic ossiculoplasty audiometric outcomes. Study Design: Retrospective review. Setting: Tertiary academic center. Patients: Adult patients who underwent ossiculoplasty with either partial ossicular replacement prosthesis (PORP) or total ossicular replacement prosthesis (TORP) from 2010 to 2019 with at least 1 year of audiometric follow-up were included. Interventions: Endoscopic or microscopic ossiculoplasty. Main Outcome Measures: Postoperative air-bone gap (ABG) after at least 1 year. Results: A total of 198 patients, 53.5% female, and a median age of 47.5 years, met inclusion criteria. 64.1% of patients were reconstructed with a PORP, and 31.8% were reconstructed using an endoscopic approach. The median audiometric follow-up was 27 months. The median postoperative ABG was 16.9 dB overall, 15.6 dB for PORP reconstruction, and 19.4 dB for TORP reconstruction (PORP versus TORP, p = 0.002). For TORP reconstructions, the median ABG for both endoscopic and microscopic TORP was 19.4 dB ( p = 0.92). For PORP reconstructions, the median ABG for endoscopic PORP was 12.3 dB compared with 16.3 dB for microscopic PORP ( p = 0.02). Using multivariate linear regression to predict postoperative PORP ABG, and controlling for age, prior ossiculoplasty, middle ear mucosal disease (granulation, fibrosis, polyposis), middle ear atelectasis, myringitis, contralateral middle ear disease, and use of byte prostheses, endoscopic PORP reconstruction was associated with improvement in ABG over the microscopic approach by 4.4 dB ( p = 0.04). Conclusions: For PORP ossiculoplasty procedures, endoscopic ossiculoplasty is associated with improved postoperative ABG compared with microscopic ossiculoplasty.